The Materials Science of Thin Films - Ohring, Milton (San Diego : Elsevier Science & Technology Books, 1991)
This is the first available textbook to provide comprehensive coverage of the science and technology of thin films and coatings. Developed for upper-level undergraduate and beginning graduate students, the book discusses physical and chemical vapor deposition processes; phenomena involving nucleation and growth, stress, diffusion and reaction; structural and chemical characterization techniques; and applications involving coatings, magnetic and optical recording materials, integrated optics, and quantum devices. The book includes chapters on epitaxy and surface modification in addition to discussing emerging technologies such as diamond films and high Tc superconductors. Complete problem sets are provided at the end of each chapter to facilitate self-study. Key Features * The first true textbook to provide broad coverage of thin films from processing to performance * Covers film materials used in microelectronics, magnetic applications, optics, and metallurgical and protective coatings * Includes chapters on epitaxy, surface modification using laser and ion beams, and emerging thin film materials and applications * Extensive treatment is given to chemical vapor deposition, diffusion and reactions, and stress in films * Provides complete exercise sets to facilitate study.
College Audience
Keywords: Thin films; Electronic books